Initial experience of visualized biliary cannulation during ERCP - Liu, Wei-hui; Huang, Xin-yu; Hu, Xiao; Wang, Pu; Yang, Yun-chao; Liu, Pei-xi; Liu, Xiao-gang (Endoscopy, 2023)
Background Selective biliary cannulation is the most challenging step in endoscopic retrograde cholangiopancreatography (ERCP) because only indirect radiographic images can be obtained. Therefore, we developed a novel endoscopic retrograde direct cholangioscopy (ERDC) technology to facilitate visible biliary cannulation.Methods In this case series, we used ERDC to treat 21 patients with common bile duct stones who were enrolled consecutively between July 2022 and December 2022. The procedure details and complications were recorded, and all patients were followed up for 3 months after the procedure. The learning curve effect was analyzed by comparing the early and later cases.Results Biliary cannulation was successful in all patients, and the stones were removed completely. The median (interquartile range [IQR]) time for cholangioscopy-guided biliary cannulation was 240.0 (10.0–430.0) seconds, and the median (IQR) number of cannulation procedures was 2 (1–5). Despite there being one episode of post-ERCP pancreatitis, one of cholangitis, and three patients developing asymptomatic hyperamylasemia, all of the patients recovered after symptomatic treatment, being discharged and with no serious adverse events occurring during the 3-month follow-up period. Compared with the early cases, the number of intubations and the use of guidewire guidance decreased in later cases.Conclusion Our research confirms that ERDC is a feasible technology for biliary cannulation under direct vision.